Strategic Marketing Plan for Summit Publishing Company Inc - Agoncillo,Charmaine Agtarap,Trixia Cunanan,Nina Monica Cunanan,Seychel Marie De Leon,Carlo Wyne Duhaylungsod,Ram Joseph and Jovero,Micca. 4 0 16; 5 (2012)
u
Strategic Marketing Plan: (BSBA msajor ni Marketing Management) - Pamantasan ng Lungsod ng Maynila 2012.
Keywords: 2 -- 0; 6; 20; 20; 2